PADDY LEAF DISEASE DETECTION USING CNN - S, Sreenivasulu; Naik, P.Pedda Sadhu (International Journal of Psychosocial Rehabilitation, 2020)
Plant diseases serve as a major threat to food supply. The proposed system helps in identification of plant disease and provides remedies that can be used as a defense mechanism against the disease. The database obtained from the Internet is properly segregated and the different plant species are identified and are renamed to form a proper database then obtain test-database which consists of various plant diseases that are used for checking the accuracy and confidence level of the project .Then using training data we will train our classifier and then output will be predicted with optimum accuracy. We use Convolution Neural Network (CNN) which comprises of different layers which are used for prediction.